PEMBENTUKAN KARAKTER RELIGIUS MELALUI KEGIATAN KEAGAMAAN DI SMA HASYIM ASY’ARI PEKALONGAN - Dyah Ayu Indra Swari; Syamsu Madyan; Eko Nasrulloh (VICRATINA, 2021)
The imact of globalization that is happening today makes people forget that character education. In fact, character education is an important national foundation to be instilled in children from an early age.. Therefore, one that is applied is the formation of the religious character of students through religious activities as in SMA Hasyim Asy'ari Pekalongan the teacher has developed a strategy for the formation of religious characters to improve students' personalities and increase students' religiousness through religious activities. Based on the research context, the researcher formulated the focus of the research, namely (1) How is the strategy for forming the religious character of students at Hasyim Asy'ari High School Pekalongan? (2) How is the implementation of religious activities in shaping the religious character of students at SMA Hasyim Asy'ari Pekalongan. (3) What are the supporting and inhibiting factors in the implementation of religious activities in shaping the religious character of students at SMA Hasyim Asy'ari.